Resection of a Petroclival Meningioma via the Endoscope-Assisted Retrosigmoid Approach: 2-D Operative Video - Lieber, Stefan; Evangelista-Zamora, Rocio; Ebner, Florian H.; Tatagiba, Marcos (Journal of Neurological Surgery Part B: Skull Base, 2018)
We present a case of a petroclival meningioma that was resected through an endoscope-assisted retrosigmoid approach via corridors above and below the facial-vestibulocochlear nerve complex. The patient is a 61-year-old female with complaints of left-sided hypesthesia and neuralgia of the infraorbital and zygomatic region, intermittent periorbital myokymia, and a slight facial palsy (HB II). This 2D video demonstrates the operative technique, anatomical and surgical nuances of the skull base approach and microdissection of the tumor from the critical neurovascular structures. A gross total resection was achieved. The patient’s facial and trigeminal symptoms resolved completely within a few weeks. At 2 year follow up there was no indication of residual or recurrence.In summary, the retrosigmoid approach with endoscopic assistance is an important and powerful tool in the armamentarium for the microsurgical management of meningiomas of the lateroventral skullbase of the posterior fossa.The link to the video can be found at: https://youtu.be/Px4XIRDoALc.
Keywords: petroclival meningioma; retrosigmoid approach; suprameatal tubercle; endoscope-assisted approach